2011
DOI: 10.1371/journal.pone.0016406
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging Reveals Different Neural Substrates for the Effects of Orexin-1 and Orexin-2 Receptor Antagonists

Abstract: Orexins are neuro-modulatory peptides involved in the control of diverse physiological functions through interaction with two receptors, orexin-1 (OX1R) and orexin-2 (OX2R). Recent evidence in pre-clinical models points toward a putative dichotomic role of the two receptors, with OX2R predominantly involved in the regulation of the sleep/wake cycle and arousal, and the OX1R being more specifically involved in reward processing and motivated behaviour. However, the specific neural substrates underlying these di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 52 publications
10
107
0
Order By: Relevance
“…Our group has recently demonstrated through a preclinical MRI approach that OX 1 R rather than OX 2 R selectively modulate mesolimbic brain region and the cortical part of the insula, areas implicated in rewarding processing (Gozzi et al, 2011). These data confirm and extend the previous findings that OX 1 R plays a role in reward processing and precipitation of drug-seeking behavior (Boutrel et al, 2005;Lawrence et al, 2006;Hollander et al, 2008;Smith et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our group has recently demonstrated through a preclinical MRI approach that OX 1 R rather than OX 2 R selectively modulate mesolimbic brain region and the cortical part of the insula, areas implicated in rewarding processing (Gozzi et al, 2011). These data confirm and extend the previous findings that OX 1 R plays a role in reward processing and precipitation of drug-seeking behavior (Boutrel et al, 2005;Lawrence et al, 2006;Hollander et al, 2008;Smith et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…Finally, the compounds were tested at the defined doses in the BE model. OX 1 R and OX 2 R antagonists are reported in the literature to be involved in the control of sleep, in particular to induce hypnotic effects (Di Fabio et al, 2011;Gozzi et al, 2011;Dugovic et al, 2009). In a preclinical hypnotic sleep model in male rats, the results obtained demonstrated that the dual OX 1 /OX 2 R antagonist, SB-649868, induced a robust hypnotic effect, both on the ability to induce and to maintain sleep, reaching a statistically significant effect at 3 mg/kg.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…D-amphetamine (0.5 mg/kg) was administered intravenously 25 min after contrast agent injection, and MRI data were acquired over a period of 25 min following the challenge. The dose of D-amphetamine was chosen based on previous in vivo studies Gozzi et al, 2011). The dose ensures robust brain activation, does not produce 'ceiling' rCBV responses (Micheli et al, 2007), and elicits transient MABP responses that are homeostatically compensated under halothane anesthesia (Gozzi et al, 2007;Zaharchuk et al, 1999).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%